Karl Kautsky on democracy and republicanism - Kautsky, Karl, 1854-1938; Lewis, Ben (Benjamin Joseph); Kautsky, Karl, 1854-1938.; Kautsky, Karl, 1854-1938.; Kautsky, Karl, 1854-1938. (Leiden ; Boston : Brill, 2020)
"Once deemed 'the pope of Marxism', Karl Kautsky (1854-1938) was the leading theoretician of the German Social Democratic Party and one of the most prominent public intellectuals of his time. However, during the twentieth century a constellation of historical factors ensured that his ideas were gradually consigned to near oblivion. Not only has his political thought been dismissed in non-Marxist historical and political discourse, but his ideas are equally discredited in Marxist circles. This book aims to rekindle interest in Kautsky's ideas by exploring his democratic-republican understanding of state and society. It demonstrates how Kautsky's republican thought was positively influenced by Marx and Engels - especially in relation to the lessons they drew from the experience of the Paris Commune"--
Introduction: Karl Kautsky's democratic republicanism -- Parliamentarism and democracy (1893) -- The Republic and social democracy in France (1905) -- The development of a Marxist (1924).
Translated from the original German into English.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 15, 2021).
eBooks on EBSCOhost
Keywords: Kautsky, Karl, -- 1854-1938.; Kautsky, Karl, -- 1854-1938; Communism -- History; Socialism -- History; Democracy; Republicanism; Representative government and representation; Républicanisme.; Gouvernement représentatif.; Communism; Democracy; Representative government and representation; Republicanism; Socialism; History